2015
DOI: 10.1186/s12864-015-2174-0
|View full text |Cite
|
Sign up to set email alerts
|

Extensive variation between tissues in allele specific expression in an outbred mammal

Abstract: BackgroundAllele specific gene expression (ASE), with the paternal allele more expressed than the maternal allele or vice versa, appears to be a common phenomenon in humans and mice. In other species the extent of ASE is unknown, and even in humans and mice there are several outstanding questions. These include; to what extent is ASE tissue specific? how often does the direction of allele expression imbalance reverse between tissues? how often is only one of the two alleles expressed? is there a genome wide bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
117
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(132 citation statements)
references
References 40 publications
14
117
1
Order By: Relevance
“…ASE occurs at heterozygous variants where one allele is more highly expressed in the mRNA than the other. Recently, Crowley et al [35] and Chamberlain et al [23] reported that 89% of mice and cattle genes, respectively, show ASE in at least one tissue. Therefore, it seems likely that cis eQTL are very common.…”
Section: Discussionmentioning
confidence: 99%
“…ASE occurs at heterozygous variants where one allele is more highly expressed in the mRNA than the other. Recently, Crowley et al [35] and Chamberlain et al [23] reported that 89% of mice and cattle genes, respectively, show ASE in at least one tissue. Therefore, it seems likely that cis eQTL are very common.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study on triploid Medaka ( Oryzias latipes ) reported that the maternally inherited allele was never silenced or suppressed, while one paternal allele was completely suppressed in the liver [23]. In cattle, tissue-specific complete suppression of either the maternally or paternally derived allele has been found [22]. In our present study, the maternal allele ( P .…”
Section: Discussionmentioning
confidence: 45%
“…formosa provides a rare opportunity to study allele-specific expression (ASE) [16] and cis -regulatory evolution in a unisexual vertebrate species with clonally inherited hybrid genomes. In humans, e.g., up to 60% of the genes show significant ASE differences or allelic bias within and between individuals, populations [1721], and tissues [22]. About 18% of all examined genes showed uneven expression between alleles in the liver of the triploid Japanese rice fish Oryzias latipes in a large-scale analysis using RNA-seq [23].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, on average the expression levels in muscle of gene pairs sharing a BiP were more correlated compared with pairs of neighbouring genes in a unidirectional or convergent configuration ( Z- score test, P -value <0.05%). Using normalized gene expression counts previously measured in 18 bovine tissues and for three different cows, 43 , 44 we calculated the Pearson correlation coefficient between the expression levels of the 120 gene pairs sharing a BiP, the 163 gene pairs in an unidirectional configuration and the 218 gene pairs in a convergent configuration. We then compared the average expression correlation between these three types of gene pairs and found no significant differences between gene pairs in unidirectional and convergent configurations, but identified significant differences between gene pairs sharing a BiP and the other two types of gene pairs ( Z- score test, P -value <0.05%), The higher correlation between expression levels of genes sharing BiPs has previously been described and is a common feature of bidirectional promoters 39 …”
Section: Resultsmentioning
confidence: 99%